Air‐Stable Wide‐Bandgap 2D Semiconductor ZnIn2S4. Issue 7 (4th May 2020) - Weng, Shirui; Zhen, Weili; Li, Yaodong; Yan, Xiu; Han, Hui; Huang, Hui; Pi, Li; Zhu, Wenka; Li, Hui; Zhang, Changjin
Abstract : The search for new 2D semiconductors with large electronic bandgap and high optoelectronic performance is pivotal for fundamental research, as such materials may lead to the scalable fabrication of optoelectronics devices. However, air‐stable 2D semiconductors with superior optoelectronic performance remain elusive at present. Herein, the discovery of ZnIn2 S4 2D semiconductor is reported, which demonstrates an attractive thickness‐dependent direct bandgap of about 2 eV. ZnIn2 S4 also exhibits excellent air stability and good optoelectronic performance, making it a promising material base for investigation of new quantum phenomena as well as for applications in the semiconductor industry. Abstract : The crystal growth and the optoelectronic properties of ZnIn2 S4 two‐dimensional semiconductor are presented, which demonstrates an attractive thickness‐dependent direct bandgap of ≈2 eV. ZnIn2 S4 also exhibits excellent air stability and good optoelectronic performance, making the ZnIn2 S4 compound a promising material base for investigation of new quantum phenomena as well as for applications in semiconductor industry.